Structure and Compatibility Study of Modified Polyurethane/Fe3O4 Nanocomposite for Shape Memory Materials - Dick Ferieno Firdaus; Masrudin Masrudin; Dessy Ayu Lestari; Mutya Rahmah Arbi; Mochamad Chalid (Universitas Gadjah Mada, 2015)
Shape Memory Polymer (SMP) is one of smart materials class that has the ability to recall a given shape before deformation in the transient state. The development of SMP is dominated by polyurethane which is currently focused on the optimization of manufacturing-related research (ease of processing), and the extraction of the potential for biomedical applications. In this study, Shape Memory Polyurethane (SMPU) with Polyethylene Glycol-based material (PEG mw: 6000) as soft segment, 4,4'-Methylenebis (Cyclohexyl isocyanate) (HMDI) as a hard segment and 1,1,1-Trimethylol propane (TMP) as a chain extender were used as a candidate for Vascular Stents. Materials used for the fillers were nano particles of magnetite (Fe3O4) which have 20–50 nm diameters. Variations of the composition were used as a variable. Fourier Transform Infrared Spectroscopy (FTIR) and Nuclear Magnetic Resonance (NMR) were conducted to investigate the polymer chains which were formed during polymerization, Field Emission Scanning Electron Microscopy (FE-SEM) was used to analyze the interface between the filler and the composite matrix. Manual physical actuation was conducted to analyze the physical recovery and transition temperature of the SMPU. Composition and fillers effect on the performance of SMPU composite were discussed in detail along with analysis of its structure and molecular design.